Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 14298 species occurrences available in GBIF matching the query: { "and" : [ "Country is Spain", { "or" : [ "TaxonKey is Narcissus bulbocodium L.", "TaxonKey is Allium melananthum Coincy", "TaxonKey is Narcissus tortifolius Fern.Casas", "TaxonKey is Iris boissieri Henriq.", "TaxonKey is Iris graminea L.", "TaxonKey is Iris lutescens Lam.", "TaxonKey is Ophrys speculum Link", "TaxonKey is Cephalanthera rubra (L.) Rich.", "TaxonKey is Orchis palustris", "TaxonKey is Epipactis palustris (L.) Crantz", "TaxonKey is Limodorum trabutianum Batt.", "TaxonKey is Orchis langei Lange ex K.Richt.", "TaxonKey is Ophrys dyris Maire", "TaxonKey is Epipactis distans Arv.-Touv.", "TaxonKey is Orchis conica Willd.", "TaxonKey is Epipactis fageticola (C.E.Hermos.) Devillers-Tersch. & Devillers", "TaxonKey is Orchis purpurea", "TaxonKey is Ophrys incubacea Bianca ex Tod., 1842", "TaxonKey is Serapias lingua L.", "TaxonKey is Serapias parviflora Parl.", "TaxonKey is Dactylorhiza fuchsii (Druce) Soó", "TaxonKey is Dactylorhiza kalopissii E.Nelson", "TaxonKey is Platanthera obtusata subsp. oligantha", "TaxonKey is Alchemilla crenulata S.E.Fröhner", "TaxonKey is Aeonium balsamiferum Webb & Berthel.", "TaxonKey is Alchemilla aranica S.E.Fröhner", "TaxonKey is Alchemilla lainzii S.E.Fröhner", "TaxonKey is Alchemilla nudans S.E.Fröhner", "TaxonKey is Alchemilla sierrae Romo", "TaxonKey is Alchemilla subalpina S.E.Fröhner", "TaxonKey is Anthyllis rupestris Coss.", "TaxonKey is Gymnocarpos decandrus Forssk.", "TaxonKey is Hieracium recoderi de Retz", "TaxonKey is Himantoglossum metlesicsianum (W.P.Teschner) P.Delforge", "TaxonKey is Helianthemum raynaudii A.Ortega, Romero García & C.Morales", "TaxonKey is Koelpinia linearis Pall.", "TaxonKey is Limonium catalaunicum (Willk. & Costa) Pignatti", "TaxonKey is Primula lofthousei Hesl.-Harr.", "TaxonKey is Silene sennenii Pau", "TaxonKey is Silene marizi Samp.", "TaxonKey is Spergularia bourgeaei Lebel", "TaxonKey is Digitalis miniana Samp.", "TaxonKey is Cerinthe glabra Mill.", "TaxonKey is Woodsia alpina (Bolton) Gray", "TaxonKey is Silaum silaus (L.) Schinz & Thell.", "TaxonKey is Senecio aquaticus Hill", "TaxonKey is Carex grioletii Roem. ex Schkuhr", "TaxonKey is Matricaria maritima L.", "TaxonKey is Prunus padus L.", "TaxonKey is Armeria cantabrica subsp. vasconica (Sennen) Uribe-Ech." ] } ] } The dataset includes 14298 records from 84 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000614-150304104939900/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences